2020
DOI: 10.1002/jia2.25546
|View full text |Cite
|
Sign up to set email alerts
|

Trends in CD4 and viral load testing 2005 to 2018: multi‐cohort study of people living with HIV in Southern Africa

Abstract: Introduction The World Health Organization (WHO) recommends a CD4 cell count before starting antiretroviral therapy (ART) to detect advanced HIV disease, and routine viral load (VL) testing following ART initiation to detect treatment failure. Donor support for CD4 testing has declined to prioritize access to VL monitoring. We examined trends in CD4 and VL testing among adults (≥15 years of age) starting ART in Southern Africa. Methods We analysed data from 14 HIV treat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 20 publications
4
37
1
Order By: Relevance
“…We found more than 75% of PLHIV in South Africa had viral load monitoring just after policy adoption, whereas coverage was less than 13% elsewhere. These findings are consistent with several recent studies, which reported disparities in viral load monitoring among income groups and countries in Southern Africa [10][11][12].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found more than 75% of PLHIV in South Africa had viral load monitoring just after policy adoption, whereas coverage was less than 13% elsewhere. These findings are consistent with several recent studies, which reported disparities in viral load monitoring among income groups and countries in Southern Africa [10][11][12].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the importance of CD4 and viral load testing, recent studies show declining pre-ART CD4 testing with HIV treatment expansion in several Southern African countries and no increases in viral load testing [10,11]. Additionally, a global study found that Treat-All adoption led to decreased pre-ART CD4 testing in low and lower-middle income countries while remaining high in upper-middle and high income countries [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its importance for guiding HIV care, since adoption of Treat-All, pre-ART CD4 testing is increasingly deprioritized in favor of scaling up viral load (VL) testing for patients on ART [ 4 , 9 , 10 ]. The US President’s Emergency Fund for AIDS Relief (PEPFAR) has reduced support for pre-ART CD4 testing—even in settings where capacity for VL testing remains suboptimal [ 3 , 5 , 10 , 11 ]—and studies suggest that pre-ART CD4 testing has decreased markedly in recent years [ 12 , 13 ], raising concerns about potential negative consequences for patient care. While VL monitoring is recommended at 6 and 12 months after ART initiation and at least annually thereafter to ascertain treatment success or failure and to guide decisions regarding regimen switches and differentiated care strategies [ 14–17 ], it is not a substitute for pre-ART CD4 testing, and it has limited value for assessing disease progression and mortality risks for patients entering or re-engaging in care [ 18 ].…”
mentioning
confidence: 99%
“…In this study, by LASSO Cox model, we found that with the increase of CD4 + T lymphocyte count, the risk of HIV seroconversion in the negative partner decreased gradually. CD4 + T cells count decline over time and are the best predictor of disease progression and risk of death, especially in patients with advanced HIV [42]. CD4 + T cells counts are used to guide some preventive and diagnostic interventions, including prioritizing detection of opportunistic infections [43].…”
Section: Discussionmentioning
confidence: 99%